Realitas Indepedensi Hakim Konstitusi dalam Pengambilan Putusan Berbasis Data Digital - Brandi Stefano Pedo; Muhamad Aldika Adha Wirya; Theo Prapaskah; Sidi Ahyar Wiraguna (Jurnal Hukum Lex Generalis, 2026)
The digital transformation within the constitutional justice ecosystem has shifted the evidentiary paradigm from conventional methods to electronic data-based systems, carrying fundamental implications for the principle of judicial independence. This study aims to analyze the reality of Constitutional Judges' independence amidst the complexity of decision-making reliant on digital data and to identify new forms of threats to judicial autonomy that are technical and psychological in nature. Employing a normative legal research method with a socio-legal approach, this study deconstructs the regulatory construction of digital evidence under the Constitutional Court Law and its derivatives, while evaluating their impact on the judicial deliberation process. The findings reveal that the absence of standardized protocols for digital data authentication and cybersecurity creates a "normative vacuum," compelling judges to rely excessively on external expert interpretations (technical dependency), thereby eroding their intellectual autonomy. Furthermore, the phenomenon of "algorithmic pressure," stemming from data-driven manipulation of public opinion on social media, is proven to induce subconscious cognitive biases that disturb the judges' internal freedom of mind. This study argues that judicial independence in the digital era can no longer be secured solely through traditional political protections; rather, it requires a conceptual reconstruction encompassing "digital sovereignty." As a solution, this research proposes the establishment of an internal Digital Forensics Center for the Constitutional Court, the enactment of Constitutional Digital Evidence Standards mandating algorithmic auditability and the ratification of a Digital Ethics Protocol to mitigate risks of subtle technology-based interventions.